2005
DOI: 10.1007/s00125-005-0060-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of insulin signalling, glucose uptake and metabolism in rat skeletal muscle cells upon prolonged exposure to resistin

Abstract: Aims/hypothesis: Debate exists regarding the role of resistin in the pathophysiology of insulin resistance. The aim of this study was to directly assess the effects of resistin (0-24 h) on basal and insulin-stimulated glucose uptake and metabolism in skeletal muscle cells and to investigate the mechanisms responsible for the effects of resistin. Methods: We used L6 rat skeletal muscle cells and examined [ 3 H]2-deoxyglucose uptake, GLUT4 translocation and GLUT protein content. We assessed glucose metabolism by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 36 publications
10
67
2
Order By: Relevance
“…The levels of neither insulin receptor β nor its phosphorylated form were altered by treatment of rat hepatocytes with resistin ( Fig. 2), results which are similar to those previously observed in muscle L6 cells (Palanivel et al 2006). IRS1 and IRS2 are two major insulin receptor effectors that contribute to the signaling that regulates glucose homeostasis (Thirone et al 2006), while tumor necrosis factor-alpha (TNFα) is an important mediator of insulin resistance in obesity and diabetes, as it induces insulin resistance at the level of the IRS proteins (Ishizuka et al 2007;Lorenzo et al 2008;Nieto-Vazquez et al 2008).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The levels of neither insulin receptor β nor its phosphorylated form were altered by treatment of rat hepatocytes with resistin ( Fig. 2), results which are similar to those previously observed in muscle L6 cells (Palanivel et al 2006). IRS1 and IRS2 are two major insulin receptor effectors that contribute to the signaling that regulates glucose homeostasis (Thirone et al 2006), while tumor necrosis factor-alpha (TNFα) is an important mediator of insulin resistance in obesity and diabetes, as it induces insulin resistance at the level of the IRS proteins (Ishizuka et al 2007;Lorenzo et al 2008;Nieto-Vazquez et al 2008).…”
Section: Discussionsupporting
confidence: 88%
“…Other studies, however, suggested that basal and insulin-stimulated glycogen synthesis was decreased in L6 rat skeletal muscle cells treated with resistin (Palanivel et al 2006;Niederwanger et al 2007). In our research, we first explored the effect of recombinant murine resistin on liver glycogen content.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…After centrifugation, pellets were dissolved in 500 μl water, 1.2 ml ethanol was added, and samples were incubated at −20°C for 20 min. Samples were centrifuged, pellets were dissolved in 500 μl water, and the radioactivity in 400 μl of solution was measured by scintillation counting [22,23].…”
Section: Glycogen Synthesis Assaymentioning
confidence: 99%